MYTHOLOGICAL CHRONOTOPAND HERO OF RUSSIAN BYLIN:PHILOSOPHICAL-CULTURAL ANALYSIS - Kasimov Ilnur Ravilevich; Rakhmanov Tazhiddin Latypovich (International Journal of Innovations in Engineering Research and Technology, 2021)
The article provides a philosophical and cultural analysis of the mythological chronotope and the heroes of Russian epics. The question of the appearance of epics, their structural and substantive features and their perception are discussed. The images of the most famous heroes of Russian epics and their path to achieving heroism are presented.